Cutaneous Manifestations of Covid-19 in Nepal: A Series of Case Reports - Prajwal Pudasaini; Gyaltsen Gurung; Asmita Paudel; Sushil Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Coronavirus Disease 2019 (COVID-19) is an illness caused by SARS-CoV-2. Case series of large population on cutaneous manifestations of COVID-19 are yet to be reported from Nepal. Among the cases in our study, onset of urticarial rash prior to onset of fever and systemic symptoms can be very important in preventing the chain of transmission of COVID-19 infection. Knowledge among medical practitioners of varied cutaneous features of COVID-19 can lead to testing COVID-19 in these cases and an early diagnosis.